Evaluasi Penerapan Kampus Berkelanjutan dengan UI GreenMetric di Universitas Andalas - Elita Amrina; Fitri Suryani (Jurnal Dampak, 2019)
University can generate a significant impact to environment due to the high usage of materials, high usage of water, high consumption of energy, massive waste, extensive transportation, and extensive development of buildings and facilities. Thus, sustainable campus is become an important issue to university. This paper evaluates the implementation of sustainable campus in Andalas University using UI GreenMetric. The metric consists of six criteria divided into 39 indicators. A questionnaire is then designed and a total of 30 experts are consulted to determine the implementation level of sustainable campus. The results indicated setting and infrastructure as the most widely implemented criterion of sustainable campus in Andalas University. Otherwise, transportation is suggested as the least implemented criterion. The suggestions are then proposed to improve the transportation criterion consisting of improving the facilities and infrastructure of campus transportation, improving the schedule of campus bus, developing the car polling program, limiting the parking area, restricting the motor vehicle, promoting the cycling and walking campaign, and developing the environmentally sound transportation. It hoped the proposed suggestions can assist the university to continously improve the sustainable campus performance.Keywords: Sustainable Campus, Transportation, UI GreenMetric, UniversityABSTRAKUniversitas dapat menghasilkan dampak yang signifikan terhadap lingkungan karena tingginya penggunaan bahan, penggunaan air yang tinggi, konsumsi energi yang tinggi, limbah yang masif, transportasi yang ekstensif, dan pengembangan bangunan dan fasilitas yang ekstensif. Sehingga kampus berkelanjutan menjadi isu penting bagi universitas. Makalah ini mengevaluasi implementasi kampus berkelanjutan di Universitas Andalas menggunakan UI GreenMetric. Ukuran yang digunakan terdiri atas enam kriteria yang terbagi menjadi 39 indikator. Kuesioner kemudian dirancang dan konsultasi terhadap 30 pakar dilakukan untuk menentukan tingkat implementasi kampus berkelanjutan. Hasil penelitian menunjukkan penataan dan infrastruktur sebagai kriteria kampus berkelanjutan yang paling banyak diterapkan di Universitas Andalas. Sebaliknya, transportasi diperoleh sebagai kriteria yang paling rendah diterapkan. Usulan perbaikan kemudian dirancang untuk meningkatkan kriteria transportasi yang terdiri atas meningkatkan fasilitas dan infrastruktur transportasi kampus, meningkatkan jadwal bus kampus, mengembangkan program polling car, membatasi area parkir, membatasi kendaraan bermotor, mempromosikan kampanye bersepeda dan berjalan kaki, dan mengembangkan transportasi yang ramah lingkungan. Usulan tersebut diharapkan dapat membantu universitas untuk terus meningkatkan kinerja kampus yang berkelanjutan.Kata kunci: Kampus berkelanjutan, transportasi, UI GreenMetric, universitas